Cardiovascular biomarkers and echocardiographic findings at rest and during graded hypovolemic stress in women with recurrent vasovagal syncope. (14th October 2019) - Lindenberger, Marcus; Fedorowski, Arthur; Melander, Olle; Gallo, Widet; Engvall, Jan; Skoog, Johan
Abstract: Introduction: Vasovagal reflex is the most common type of syncope but its etiology is not fully elucidated. Venous return and cardiac output are key in hemodynamic control. The aim of the study was to assess cardiovascular biomarkers and echocardiographic measures at rest and during hypovolemia in women with and without a history of vasovagal syncope. Methods: Fourteen women (aged 18‐30) suffering from recurrent vasovagal syncope and 15 age‐matched healthy women were included. Graded lower body negative pressure (LBNP) was used to create central hypovolemic stress until signs of presyncope occurred. Echocardiography was applied at rest and throughout LBNP. Cardiovascular biomarkers: copeptin, mid‐regional proadrenomedullin, mid‐regional pro‐ANP, C‐terminal proendothelin‐1, and plasma norepinephrine were measured both at rest and throughout graded hypovolemia to presyncope. Results: Women prone to vasovagal syncope presented with a narrower right ventricle (RV) (29 ± 1 vs 32 ± 1 mm, P < .05), smaller left atrium (36 ± 2 vs 47 ± 3 cm 3, P < .01) and lower cardiac output at rest (3.1 ± 0.2 vs 3.7 ± 0.2 L/min, P < .05) and during graded hypovolemia ( P < .05). Copeptin was elevated at rest (4.3 ± 0.8 vs 2.5 ± 0.2 pmol/L, P < .05) and increased more in women with vasovagal syncope during progression of LBNP ( P < .01). At rest, lower C‐terminal proendothelin‐1 (35 ± 5 vs 46 ± 2 pmol/L, P < .05) and higher norepinephrine levels (1.1 ± 0.1 vs 0.8 ± 0.1 nmol/L, P < .01) were seen in women with vasovagal syncope. Conclusion: Women prone to vasovagal syncope demonstrate reduced cardiac preload, lower cardiac output, as well as increased release of vasopressin in rest and during hypovolemic challenge. The results emphasize the importance of venous return and cardiac output in the pathogenesis of vasovagal syncope.